The neuronal chaperone proSAAS is highly expressed in the retina - Nicholas Schaffer; Samira Mitias; Yan Guo; Steven L. Bernstein; Iris Lindberg (PLoS ONE, 2025)
The many layers of the neuroretina contain a complex, interconnected network of specialized neurons that both process visual stimuli and conduct processed information to higher brain areas. Neural networks rely on proteostatic control mechanisms to maintain proper protein homeostasis both in cell bodies as well as within synapses; protein chaperones play an important role in regulating and supporting this process. ProSAAS is a small neuronal chaperone that functions as an anti-aggregant in in vitro assays and is released upon depolarization in neuronal primary cultures. We here report a potential role for proSAAS in the retina. A review of human and mouse retinal RNAseq studies reveals that proSAAS expression is abundant within the retina. Single cell sequencing data from mouse and human studies show that proSAAS levels are highest in retinal ganglion cells (RGCs) and horizontal cells. Using proSAAS antibodies in combination with antisera to known retinal cell markers in mouse retinal sections, we confirm RNAseq data showing that proSAAS expression is highest in RGCs and horizontal cells. The proSAAS signal is concentrated within the ganglion cell layer and the inner plexiform layer, a dense synaptic layer connecting retinal neurons. Western blotting of mouse retinal extracts indicates the presence of two processed proSAAS forms, a 21 kDa C-terminally processed form, and a small 13 kDa species which, based on antibody specificity, likely represents an internal fragment. This fragment is also found in extracts prepared from human retinas. Taken together, our data provide support for the hypothesis that retinal synapses utilize the proSAAS chaperone to support visual signaling.